IMPROVING ORGANIZATIONAL CITIZENSHIP BEHAVIOR THROUGH ORGANIZATIONAL CLIMATE, PERSONALITY AND JOB SATISFACTION OF FUNCTIONAL POSITION EMPLOYEES - Andrianto, Muhammad Tito; Moeins, Anoesyirwan; Sunaryo, Widodo (UTSAHA: Journal of Entrepreneurship, 2023)
Organizational citizenship behavior is critical since employees with a high level of it are considered to be more innovate, provide their best service, and can create a comfortable atmosphere in the organization. Moreover, organizations that have employees with high levels of organizational citizenship behavior will tend to have high performance and more easily achieve organizational goals. This research aims to empirically examine the relationship between organizational climate, personality, and job satisfaction variables with organizational citizenship behavior (OCB) of functional employees of Immigration Office. This research uses job satisfaction as an intervening variable. This research is sequential explanatory, which combining qualitative and quantitative analysis. The sample in this research was selected using a proportional random sampling method with a total of 268 respondents. The data collection was conducted by distributing questionnaires, focus group discussions (FGD), and triangulation of human resource experts. The results shows that organizational climate, personality, and job satisfaction have a positive and significant influence on OCB. In addition, the results also indicated that the role of job satisfaction variables as intervening was not significant in influencing the relationship between organizational climate and personality to improve the OCB.